2015
DOI: 10.3389/fnhum.2015.00565
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal frontostriatal activity in recently abstinent cocaine users during implicit moral processing

Abstract: Investigations into the neurobiology of moral cognition are often done by examining clinical populations characterized by diminished moral emotions and a proclivity toward immoral behavior. Psychopathy is the most common disorder studied for this purpose. Although cocaine abuse is highly co-morbid with psychopathy and cocaine-dependent individuals exhibit many of the same abnormalities in socio-affective processing as psychopaths, this population has received relatively little attention in moral psychology. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 155 publications
(183 reference statements)
0
8
1
Order By: Relevance
“…Significant brain effects at the whole-brain level were found in 95% of studies. Independent of the task (passive viewing, non-emotional or emotional) and valence of the stimuli (pleasant or unpleasant), studies consistently reported a downregulation of the reward (ventral striatum, rACC/sgACC, dmPFC, OFC and aPFC) , salience (anterior insula, dACC, IPL) and executive (vlPFC/dlPFC) networks during social-emotional processing, often accompanied by reduced recruitment of the memory (hippocampus/parahippocampus) and self-directed (PCC/precuneus) networks (Asensio et al, 2010; Caldwell et al, 2015; Canterberry et al, 2016; Costumero et al, 2017; Gilman et al, 2010; Hong et al, 2017; Kim et al, 2014; Landi et al, 2011; Maurage et al, 2012; Payer et al, 2012, 2011; Roberts and Garavan, 2013; Seo et al, 2013; Wesley et al, 2016; Suppl. Table 1, Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant brain effects at the whole-brain level were found in 95% of studies. Independent of the task (passive viewing, non-emotional or emotional) and valence of the stimuli (pleasant or unpleasant), studies consistently reported a downregulation of the reward (ventral striatum, rACC/sgACC, dmPFC, OFC and aPFC) , salience (anterior insula, dACC, IPL) and executive (vlPFC/dlPFC) networks during social-emotional processing, often accompanied by reduced recruitment of the memory (hippocampus/parahippocampus) and self-directed (PCC/precuneus) networks (Asensio et al, 2010; Caldwell et al, 2015; Canterberry et al, 2016; Costumero et al, 2017; Gilman et al, 2010; Hong et al, 2017; Kim et al, 2014; Landi et al, 2011; Maurage et al, 2012; Payer et al, 2012, 2011; Roberts and Garavan, 2013; Seo et al, 2013; Wesley et al, 2016; Suppl. Table 1, Figure 4d).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1, Figure 4d). Well-controlled studies using narrow contrasts and active task paradigms (Caldwell et al, 2015; Maurage et al, 2012) or highly salient stimuli (e.g., infant cries or erotic stimuli: Costumero et al, 2017; Landi et al, 2011) generally showed the most extensive effects implicating several brain networks. Compared to nicotine/cocaine addiction, brain effects in alcohol/cannabis addiction were somewhat less extensive, with specifically the reward network being less consistently implicated (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Together, these and many other studies highlighted changes in functional connectivity during resting or task challenges in cocaine misuse ( Adinoff et al, 2015 ; Albein-Urios et al, 2014 ; Barros-Loscertales et al, 2011 ; Caldwell et al, 2015 ; Cisler et al, 2013 ; Hu et al, 2015c ; Konova et al, 2015 ; Ma et al, 2014 ; McHugh et al, 2014 ; Ray et al, 2015a ; Wisner et al, 2013 ; Zhang et al, 2014 ). The great majority of these studies focused on specific regions of interest, and none examined the dynamic aspects of functional connectivity ( Cohen, 2017 ).…”
Section: Introductionmentioning
confidence: 68%
“…In one study, cocaine users who were participating in an inpatient treatment program, relative to non-cocaine users, showed lower task related activity in the dorsal ACC while evaluating moral dilemmas (Verdejo-Garcia et al 2014). Additionally, in previous work we found that abstinent, incarcerated cocaine-users, relative to non-using incarcerated controls, had lower activation in the ACC and vmPFC during implicit moral processing (Caldwell et al 2015). Implicit moral processing triggers automatic moral processes but does not have moral task demands (e.g., shows a picture of a murder scene and asks if the scene is inside or outside.)…”
mentioning
confidence: 67%
“…Only two studies to date have directly examined how stimulant users’ brains process morally-salient stimuli (Caldwell et al 2015; Verdejo-Garcia et al 2014). In one study, cocaine users who were participating in an inpatient treatment program, relative to non-cocaine users, showed lower task related activity in the dorsal ACC while evaluating moral dilemmas (Verdejo-Garcia et al 2014).…”
mentioning
confidence: 99%